Faith – Reason: a Problematic Relationship? Theology as an Extension of Faith in Reason - Marcelo Javier Navarro Muñoz (Polonia Sacra, 2021)
In this article the author reviews the interrelationship between faith and reason in the steps of John Paul II’s Encyclical Letter Fides et ratio. He explores briefly historical circumstances following Etienne Gilson. Then, he introduces philosophical and theological considerations of Cornelio Fabro to do theology in the footsteps of Aquinas. From the perspective of Thomism of the Italian philosopher and by recalling the most urgent theological tasks for the third millennium as indicated in Fides et ratio, the author presents general guidelines for the circularity of faith and reason within the context of fundamental theology. Throughout this article he reads Fides et ratio specifically through the Fabrian lens to present a fresh perspective as a contribution to fundamental theology. Finally, he recalls the conclusive recommendation of John Paul II in the aforementioned letter so as to harmonize reason and faith within a Marian framework.